Role played by girl characters in Sepedi folktales - Seboni, Ntoro Charlotte (University of Limpopo ( Turfloop campus), 2010)
Refer to document
Thesis (M.A.(Folktales studies)) --University of Limpopo, S.A , 2011
Keywords: Characters; Folktales; 398.20496; Folklore,Pedi